Riboflavin Production by Steady-State Continuous Cultures of Hyphopichia wangnamkhiaoensis in a Bubble Column Bioreactor - Raziel Arturo Jiménez-Nava; Griselda Ma. Chávez-Camarillo; Eliseo Cristiani-Urbina (Microorganisms)
Riboflavin is biosynthesized and excreted extracellularly by the novel yeast Hyphopichia wangnamkhiaoensis. The steady-state kinetics of cell growth, substrate consumption, and riboflavin production by H. wangnamkhiaoensis were studied in a chemostat continuous culture at different dilution rates. The unstructured Monod and Luedeking–Piret models were used to describe cell growth, substrate consumption, and riboflavin production, and crucial kinetic parameters were estimated. The experimental data fitted the proposed models well. The maximum specific growth rate, substrate affinity constant, maintenance energy coefficient, and maximum biomass yield values were 0.1378 h−1, 0.4166 g of glucose L−1, 0.1047 g of glucose g−1 of biomass h−1, and 0.172 g of biomass g−1 of glucose, respectively. The maximum yield from glucose and volumetric and specific productivities of riboflavin were 0.7487 mg of riboflavin g−1 of glucose, 0.5593 mg of riboflavin L−1 h−1, and 0.6547 mg of riboflavin g−1 of biomass h−1, respectively. The estimated growth-associated riboflavin production constant (4.88 mg of riboflavin g−1 of biomass) was much higher than the non-growth-associated riboflavin production constant (0.0022 mg of riboflavin g−1 of biomass h−1), indicating that riboflavin production by H. wangnamkhiaoensis is a predominantly growth-associated process. The chemostat continuous culture offers a promising strategy for efficiently and sustainably producing riboflavin using H. wangnamkhiaoensis.